Development and maintenance of the special course «Formation of the conscious relation to the nature at the preschool children living in conditions of radiation pollution» - Комарова, И. А; Спирин, С. В. (Scientific notes of the pedagogical department, 2018)
The article reveals the issue of the organization and content of students of higher education institutions preparation to the radioecology of preschool children as one of the most relevant and complex problem in higher education. The authors pay special attention to the selection and characterization of the main components of the future teachers training on radioecological education of preschool children in a pre-school educational institution. Within the definition of the optimal content of the option course «Formation of a conscious attitude towards nature in preschool children living in conditions of radiation pollution», the issues of environmental education of preschool children, including the formation of ecological consciousness, a careful attitude to nature and the surrounding reality, are considered. The authors emphasize that the main goal of the option course is to assist students – future teachers of the specialty «Preschool education» in mastering the knowledge system in the field of radioecological education in the Republic of Belarus and the region, to determine the main radioecological concepts and the ways of professional skills growth of the future specialist in radiological education of children and their parents. In this paper, the authors disclose a developed and tested series of simulation game learning situations. It is proved that simulated game learning situations used during lectures and practical session contribute to the effective accumulation of professional knowledge. The study conducted by the authors suggests that interactive learning during the study of the option course significantly increases the level of mastering the educational material, allows you to master the content and innovative technologies of the educational process in the modern preschool educational institution, to acquire the culture of communication management, discussion, as well as collective mental activity, to develop communicative, expert, reflexive abilities, qualitatively master the professional functions of the pre-school teacher.